Occupancy and overlap in trait space along a successional gradient in Mediterranean old fields. Issue 6 (15th June 2016) - Loranger, Jessy; Blonder, Benjamin; Garnier, Éric; Shipley, Bill; Vile, Denis; Violle, Cyrille
Abstract : PREMISE OF THE STUDY: Secondary succession is a worldwide phenomenon affecting plant communities. Studying functional variation during succession aids in understanding the mechanisms through which environmental shifts drive succession. We investigated changes in the functional space occupied by herbaceous communities during succession. Furthermore, since different traits are differently affected by environmental conditions, we asked how considering different sets of plant traits impacts those changes. METHODS: Using a chronosequence of Mediterranean old fields (2–42 yr after abandonment), we analyzed shifts of the occupied functional space during succession, how the volume of occupied functional space varies compared with null expectations, and the functional overlap between communities of different successional status. We repeated these analyses considering (1) the leaf–height–seed functional dimensions separately and together and (2) different sets of traits representing those dimensions. KEY RESULTS: From early to late succession, a shift toward nutrient conservative‐light competitive species occurred. Functional strategies of mid‐successional communities appeared more diverse than expected by chance and less diverse than expected for early and late communities. Early and middle stages overlapped the most. These patterns were generally robust to the choice of functional axes, though important trait‐specific exceptions occurred. CONCLUSIONS: We showed evidence for a well‐defined history of successive dominance of different assembly mechanisms along succession, resulting in a generally stronger functional diversification in mid‐succession. We also demonstrated that different traits typically grouped under one functional dimension can substantially affect the results, discouraging the use of surrogate traits from the same dimension.